Practice of Islamic Education Teachers of Prophetic Methods in Arousing Motivation When Teaching the Holy Quran in the Primary Stage in Jeddah Governorate - Alsahli, Abdulaziz Abdullah (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to identify the degree of practice of Islamic education teachers of the Prophet's methods in raising motivation when teaching the Holy Qur'an in the primary stage in Jeddah Governorate, the research used the descriptive approach based on the survey method, and to achieve the objectives of the research, a list of (30) paragraphs was prepared that includes the prophetic methods used to raise motivation when teaching the Holy Qur'an, and then the procedures for honesty and stability of the tool containing the prophetic methods in raising motivation were ensured, and the study population consisted of (35) supervisors of Supervisors of Islamic education in Jeddah Governorate, the study tool has been applied to all the study community, and the research found that the degree of practice of Islamic education teachers of the Prophet's methods in raising motivation when teaching the Holy Quran was high in all its fields "mentioning the benefits of learning the Holy Quran, highlighting models and examples, providing various reinforcers" In the field of "diversification of methods and teaching methods", the degree of practice of Islamic education teachers was average, and in light of the findings of the research, a number of recommendations were made from the most important of which is the design of programs for teaching the Holy Quran, which focuses on diversifying the use of teaching methods and methods, which the results of the research indicated that they were received to a medium degree, and also providing various educational resources that enhance the visibility of models and role models, such as stories, situations, realism, songs, and educational films, and the research was concluded by providing several suggestions for future studies that benefit researchers in the same field, most notably conducting a study with an experimental approach that measures the impact of using prophetic methods in raising the motivation of learning the Holy Qur'an Students in the three educational stages (primary, intermediate, secondary).
Keywords: Islamic education; prophetic methods; motivation; teaching the Holy Quran; primary stage